Problematyka filozoficzna w dorobku pisarskim Wojciecha Tylkowskiego SJ - Lisiak, Bogdan (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article presents the issue of philosophy and science cultivated by the Polish Jesuit, Fr Wojciech Tylkowski (1624-1695), a polymath viz. scientist of many varied interests. Tylkowski acted primarily as an educator and lecturer in philosophy at schools run by the Jesuit Order. Tylkowski aspired toward mastering all philosophical and natural science known to him. The notion of the complete scholar of the baroque period – the homo universalis – was a crucial factor in his way of thinking and scientific work. The synthesizing of all knowledge known to him marked the purpose of his writing. For this very reason he also led independent studies, which resulted in his writing activity in the fields of philosophy, theology, astronomy, mathematics, geography, technology, art, and even agriculture. Tylkowski practised philosophy in the spirit of the Aristotelian-Scholastic tradition. An important area of his writing initiative is the so-called philosophia curiosa , understood as philosophy that evokes in the mind of the recipient an interest in the world and knowledge of the subject. Tylkowski was an original representative of this style of practising philosophy and science. His books, especially those written in the popularized convention, the philosophia curiosa , were directed towards a wide circle of readers.